The nature of a poetic collection in the poetry of samandar vokhidov - G.N. Zoyirova (International Journal on Human-Computing Studies, 2021)
The article provides a theoretical analysis of the series " Haj daftari " by the poet SamandarVahidov. This series is compared with the series of the same name by the folk poet of Uzbekistan Abdulla Aripov. Their differences and similarities are explained in terms of the concept of diversity.